(untitled) (Medical Forum Monthly, 2024)
Objective: Objective of the study is to identify risk factors for Acute Myocardial Infarction (AMI). Study Design: Prospective cross sectional study Place and Duration of Study: This study was carried out at AK CMH/SKBZ Muzaffarabad from August 2012 to September 2013. Materials and methods: This study of first ever AMI patients was carried out in a tertiary care teaching hospital. Standard methods were followed to elicit risk factors. Chi-square and Fishers exact tests on SPSS 20 were done for analysis of risk factors. Result: A total of 210 patients (male (M) = 118and female (F) = 92) with age range from 30 to more than70 years were included. The mean age of patients was 56.30±13.79 years. The risk of developing AMI was statistical significantly in both males and female (<0.001). The significant risk factors for all AMI were: Hypertension (p=0.039), diabetes (p=0.001), Hypercholesterolemia (p=0.05), smoking (p=0.001) and family history of AMI (p=<0.001).Age ( p=<0.001 and age category (p=0.045) were also identified as statistical significance risk factor for AMI. Mortality was 24 (11.4%). Conclusion: Thus we conclude that CAD is more common in adult and has significant association with modifiable major risk factors in our population. Targeted interventions that reduce/modify these modifiable CAD risk factors could substantially reduce the mortality and morbidity of AMI. Health educations on life style modification, programs to diagnose, control of diabetes, hypercholesterolemia and hypertension have to be initiated at community level in order to reduce the occurrence.